Micrographic Analysis of SMAW Welding (Revista Cientifica Ingenio Magno, 2025)
The study focuses on analyzing the microstructure of low-carbon AISI 1020 steel after being subjected to the Shielded Metal Arc Welding (SMAW) process. For this purpose, samples were prepared from both the base material and the heat-affected zones (HAZ) produced during welding. The specimens were mounted in polyester resin, polished, and chemically etched with a 5% Nital solution, which allowed the phases present in the material—such as ferrite, pearlite, and martensite—to be highlighted. Using a metallographic microscope, images were captured at different magnifications (100x, 200x, and 400x), showing that areas near the weld bead in the base material exhibited a ferritic matrix with dispersed pearlite and a fine grain size; in the HAZ grain growth and acicular morphologies compatible with high cooling-rate transformations (bainite/martensite) were observed; while the weld bead showed columnar grains with a predominance of ferrite and a lower pearlitic fraction. These results allow a correlation to be established between the welding process parameters and the microstructural changes, which is essential for optimizing the quality and integrity of welded joints.
Keywords: Ferrite, Metallography, Pearlite, SMAW, Electric welding